2016
DOI: 10.1038/srep27801
|View full text |Cite
|
Sign up to set email alerts
|

Treatment by glyphosate-based herbicide alters life history parameters of the rose-grain aphid Metopolophium dirhodum

Abstract: Glyphosate is the number one herbicide in the world. We investigated the sub-lethal effects of this herbicide on the aphid Metopolophium dirhodum (Walker), using an age-stage, two-sex life table approach. Three concentrations of the herbicide (low - 33.5, medium - 66.9 and high - 133.8 mmol dm−3 of active ingredient) and distilled water as the control were used. The LC50 of the IPA salt of glyphosate on M. dirhodum was equivalent to 174.9 mmol dm−3 of the active ingredient (CI95: 153.0, 199.0). The population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…We had only female aphids in our population. How- (Saska et al 2016). The approach has been used also earlier for one-sex aphid studies by e.g.…”
Section: Life Table Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We had only female aphids in our population. How- (Saska et al 2016). The approach has been used also earlier for one-sex aphid studies by e.g.…”
Section: Life Table Analysismentioning
confidence: 99%
“…The approach has been used also earlier for one-sex aphid studies by e.g. Akca et al (2015), Akköprü et al (2015) and Saska et al (2016). The developmental time, age-stage specific survival rate (s xj ), age-specific survival rate (l x ), age-stage specific fecundity (f xj ), age-specific fecundity (m x ), age-specific net fecundity (l x m x ), intrinsic rate of increase (r), finite rate of increase (l), net reproductive rate (R 0 ) and mean genera- tion time (T) were calculated using the TWO-SEX-MSChart program (Chi 2016a) as described by Chi and Su (2006), Tuan et al (2014a, b) and Chi et al (2016).…”
Section: Life Table Analysismentioning
confidence: 99%
“…The age-stage, two-sex life table approach can provide more accurate estimates of population parameters, given that this approach considers both sexes and the variable developmental rate among individuals and can properly describe the development, stage differentiation, survival, and reproduction of the population [ 21 – 23 ]. It has been widely used to examine the responses of various herbivore species to doses and/or concentrations of insecticides [ 14 , 23 26 ]. For example, when M .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time residues of glyphosate and its primary metabolite aminomethylphosphonic acid (AMPA, Figure 5) were detected in the soil, in freshwater, and in the organisms that live there (Perez et al, 2011), in the crop products, in the animals that were fed with them, and in humans, too. Therefore, studies were initiated to determine whether continuous exposure to glyphosate leads to unwanted effects to the environment, such as soil microorganisms (Kremer and Means, 2009), insects (Saska et al, 2016), fish (Giannini, 2013), and to humans. Results of these studies were presented in a number of papers (Szekacs and Darvas, 2012;Myers et al, 2016;Mensah et al, 2015) and discussed in excellent books (to mention one: Nandula, 2010).…”
Section: Fate In the Environment And Side Effectsmentioning
confidence: 99%
“…), pathogen-degrading enzymes, and deliberate cell suicide (hypersensitive reaction, HR) (Barna et al 2012). Saska et al (2016) found that population parameters of the aphid Metopolophium dirhodum were significantly negatively affected by applications of sub-lethal doses of glyphosate. Glyphosate, by blocking the synthesis of chorismic acid (and the aromatic amino acids) may negatively influence virtually all of the induced defense plant responses, and, after longer times of exposure, even the constitutive ones.…”
Section: Effects On Plant-pathogen Interactionsmentioning
confidence: 99%